Optimalisasi Kualitas Citra Coronal Tracking CT Urografi Non Kontras Dengan Variasi Teknik Rekonstruksi iDose4 dan Iterative Model Reconstruction (IMR) - Faik, Muhamad; Yusnida, Arnefia Mei (Jurnal Imejing Diagnostik (JImeD), 2025)
Background: Non-contrast urography CT images with iDose4 level 6 reconstruction techniques produce the best and lowest diagnostic information compared to FBP, iDose4 level 1, iDose4 level 2, iDose4 level 3, iDose4 level 4, iDose4 level 5 (Faik, 2023). The next generation of advanced reconstruction techniques that came after iDose4 is IMR capable of producing images that are free of noise (Halliburton, 2016). The purpose of the study was to determine the settings of the reconstruction technique that produces the lowest noise and the best diagnostic information.Methods: This research is an experimental research conducted at the Salatiga City Hospital on November 2024. The noise was obtained from the results of measurements by 3 radiographers using ROI. Diagnostic information was obtained by providing a checklist to 3 radiologists. Data analysis was carried out by a statistical test of friedman.Results: The image with iDose4 level 6 has the highest noise of 8.67, IMR level 1 has an noise of 5.68, IMR level 2 has an noise of 2.89, and IMR level 3 has the smallest noise of 1.09. Meanwhile, the image with iDose4 level 6 reconstruction technique has the highest diagnostic information of 3.00, IMR level 1 has an diagnostic information of 2.67, IMR level 2 has an diagnostic information of 2.22, and IMR level 3 has the smallest diagnostic information of 1.55.Conclusions: The image with IMR level 3 had the lowest noise of 1.09 and the image with iDose4 level 6 had the best diagnostic information of 3.00.